The language of beauty in African art - Petridis, Constantine 1970-; Petridis, Constantine 1970-; Biro, Yaëlle 1979-; Cole, Herbert M.; Kone, Kassim; Lawal, Babatunde 1942-; Damme, Wilfried van; Vogel, Susan Mullin 1942- (The Art Institute of Chicago, 2022)
This ambitious publication centers indigenous perspectives on traditional artworks from Africa by focusing on the judgments and vocabularies of members of the communities who created and used them. It explores cross-cultural affinities spanning the African continent while respecting local contexts; it also documents an exhibition that is extraordinary in scope and scale. The project's overriding goal is to reconsider Western evaluations of these arts in both aesthetic and financial terms. The volume features nearly 300 works from collections around the world and from the important holdings of the Art Institute of Chicago. Although it emphasizes the sculptural legacy of sub-Saharan cultures from West and Central Africa, it also includes examples of artistic traditions associated with eastern and southern Africa as well as textiles and objects designed for domestic, ritual, and decorative functions
Aus dem Impressum: "'The language of beauty in African art' was published in conjunction with an exhibition of the same title organized by the Art Institute of Chicago. Kimbell Art Museum, Fort Worth, Texas, April 3 - July 31, 2022. The Art Institute of Chicago, November 20, 2022 - February 27, 2023"
Keywords: Kunst; Subsaharisches Afrika; Aesthetics, African / Exhibitions; Art, African / Exhibitions; Sculpture, African / Exhibitions; Esthétique africaine / Expositions; Art africain / Expositions; Sculpture africaine / Expositions; PHILOSOPHY / Aesthetics; Aesthetics, African; Art, African; Sculpture, African; Exhibition catalogs; Illustrated works; Ausstellungskatalog -- Kimbell Art Museum -- 03.04.2022-31.07.2022 -- Fort Worth, Tex.; Ausstellungskatalog -- Art Institute of Chicago -- 20.11.2022-27.02.2023 -- Chicago, Ill.; Bildband